Proposed New Services And Marketing Strategy For Mavens Studio - Imaduddin Islam, Ibrahim; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract. Indonesia is a country that known as active internet user. In Early 2015, 72,7 million Indonesia (or 28% of total population) are active in using internet. Todays, people not only using internet for accessing news portal or searching an information, but also they using internet to do a lot of things like online shopping, playing games or accessing a social network. 62 million of which social media account are accessing via mobile Since 2008, a huge number of start up company, especially digital start up are rising. It’s possible for Indonesia being the next Silicon Valley in South East Asia. The development of technology, growth of start up company, and growth of internet user in Indonesia make video being important on digital marketing strategy todays. This situation make Mavens Studio, a company founded in Bandung in 2013 are encouraged to develop its business in the creative industry. Unfortunately, since company appearance, Mavens Studio have a low profit with no marketing effort. To find the roots of these problems the author used PEST, Segmenting, Targeting and Positioning (STP); Marketing Mix and SWOT analysis. From the analysis conducted, it can be concluded that the root of the problem that makes his sales and profit are low, the unclear positioning of the company. To solve the root of the problem, a solution that will be used is by changing the Segmenting, Targeting and Positionong and propose new marketing mix (Product, Price, Place, Promotion, People). Changes occur segmenting in terms of, Type of the client, distribution channel, size of channel, location and consumer behavior. Mavens Studio also change its targeting and positioning. Changes in the STP is the basis of changes in the marketing mix. Some programs of the marketing mix that will be done include creating new services that is Startup, City and Political Branding Services with new price package, rent new office in Jakarta, creating online portfolio, improving social media marketing concept, making a strategic partnership and collaboration project also made system restructuring with a new permanent employee and intern. An implementation plan is made in the form of a table plan. Implementation plan covering time and budget. This implementation began in July 2016 through December 2017. Keywords: Branding Consultant, Sales, STP, Marketing Mix